Enantioselective Synthesis of α‐Thiocarboxylic Acids by Nitrilase Biocatalysed Dynamic Kinetic Resolution of α‐Thionitriles. Issue 46 (16th July 2020) - Lauder, Kate; Anselmi, Silvia; Finnigan, James D.; Qi, Yuyin; Charnock, Simon J.; Castagnolo, Daniele
Abstract: The enantioselective synthesis of α‐thiocarboxylic acids by biocatalytic dynamic kinetic resolution (DKR) of nitrile precursors exploiting nitrilase enzymes is described. A panel of 35 nitrilase biocatalysts were screened and enzymes Nit27 and Nit34 were found to catalyse the DKR of racemic α‐thionitriles under mild conditions, affording the corresponding carboxylic acids with high conversions and good‐to‐excellent ee . The ammonia produced in situ during the biocatalytic transformation favours the racemization of the nitrile enantiomers and, in turn, the DKR without the need of any external additive base. Abstract : Nitrilase biocatalysts catalyse the dynamic kinetic resolution (DKR) of α‐thionitriles affording enantiomerically pure α‐thiocarboxylic acids under mild conditions. The DKR is favoured by the ammonia formed in situ during the biotransformation.